Excerpts on the History of Mother and Infant Protection in Moscow at the beginning of the 20th century - Larisa E. Gorelova; Vera N. Shelkova (Вопросы современной педиатрии)
The article is devoted to the important course of the medicine development at the beginning of the 20th century — mother and infant protection. The contribution of pediatricians and obstetricians to prevention of high infant mortality in Moscow is represented. The activities of G.N. Speransky and other doctors in public benevolent institutions are reported.